Factors Associated with Non-Adherence to Antipsychotic Medication among Adult Patients with Schizophrenia: A Cross-Sectional Study - Omar Murtaza Sheikh, Ghulam Shabir Shaikh, Naeem Amjad, Ashfaq Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to assess the factors associated with non-adherence to antipsychotic medication in adult patients with schizophrenia. Methods: A total of 135 adult patients diagnosed with schizophrenia were recruited for this study. We conducted structured interviews and analyzed patient records to gather data on demographic characteristics, clinical factors, medication-related variables, and psychosocial factors. A multivariate analysis was performed to identify significant predictors of non-adherence. Results: The findings revealed that factors such as poor insight into the illness (p<0.01), medication side effects (p<0.05), and substance abuse (p<0.05) were significantly associated with non-adherence. Other contributing factors included socioeconomic factors such as lower income and education (p<0.05) and the complexity of the medication regimen (p<0.05). Conclusion: Non-adherence to antipsychotic medication is influenced by a range of factors, including clinical, medication-related, and socioeconomic factors. Addressing these factors through targeted interventions could improve medication adherence and overall patient outcomes. Keywords: schizophrenia, non-adherence, antipsychotic medication, insight, substance abuse, socioeconomic factors